Keep Calm and Be a Dad: Psychosocial Factors and Fathers’ Emotional Well-Being (Studia Doctoralia Psychology and Educational Science, 2025)
The aim of this study was to examine how perceived social support (PSS), parental competence (PC), and parenting styles affect Romanian fathers’ psychological well-being - as indicated by symptoms of depression, anxiety, and stress - and how these relationships are moderated by marital status, levels of neuroticism, and time spent with children. Using a cross-sectional design, the research was conducted on a nonclinical sample of 106 Romanian fathers (M = 42.15 years, SD = 7.33), of whom 66 were married and 40 were divorced or separated. Participants completed an online battery of questionnaires represented by MSPSS, PSOC, PSDQ-short, IPIP-Ro neuroticism, and DASS-21. Results showed that higher perceived social support was associated with significantly lower depressive symptoms and showed smaller, context-dependent associations with anxiety and stress.Parental competence emerged as a robust predictor of reduced depression and stress, with no modulation by marital status or time spent with children. Marital status significantly moderated the link between social support and depression: the protective effect of social support was stronger among married fathers than among divorced/separated fathers.
Keywords: perceived social support; parental competence; parenting styles; depression; anxiety; stress; marital status; neuroticism; fathers’ mental health